2022
DOI: 10.22146/jpki.71840
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Students’ Engagement Using Interactive Applications in Online Lectures

Abstract: Background: Online lectures are now increasing in popularity for medical education worldwide. Online lectures were reported effective and efficient and might facilitate a safe learning environment with physical distancing during the COVID-19 pandemic. To date, there is a range of online meeting applications available, namely, Zoom®, GoogleMeet®, Webex®, and many others. The main challenge of online lectures is ensuring students’ engagement throughout the learning activity. Lecturers possess lower control of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…The results of data analysis demonstrated that the majority of educators perceived that the Mentimeter platform is useful for increasing students, engagement in online synchronous courses. This result seems to be consistent with those of some previous studies (e.g., Vallely and Gibson, 2018;Moorhouse and Kohnke, 2020;Demirci et al, 2021;Sari, 2021;Mohin et al, 2022;Utomo and Utama, 2022). The results of our study also indicated that the attitudes of the participants were favorable toward the usage of the Mentimeter platform in synchronous online instruction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of data analysis demonstrated that the majority of educators perceived that the Mentimeter platform is useful for increasing students, engagement in online synchronous courses. This result seems to be consistent with those of some previous studies (e.g., Vallely and Gibson, 2018;Moorhouse and Kohnke, 2020;Demirci et al, 2021;Sari, 2021;Mohin et al, 2022;Utomo and Utama, 2022). The results of our study also indicated that the attitudes of the participants were favorable toward the usage of the Mentimeter platform in synchronous online instruction.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Anggriani et al (2022) used a quasi-experimental method to investigate how the problem-based learning model with the integration of a Mentimeter affects improving elementary students' critical thinking and collaboration skills. In the same context, a recent review about the use of Mentimeter's quizzes and online surveys as interactive applications to increase students' engagement during online lectures conducted by Utomo and Utama (2022) recommended the utilization of interactive applications be carefully prepared to ensure good student engagement but not overly used to prevent any possible distractions. In addition, they came to the conclusion that survey and interactive presentation applications are available to improve classroom and online lecture engagement.…”
Section: Literature Reviewmentioning
confidence: 99%